Analisis Visualisasi Aliran Pengujian Model Airfoil Menggunakan Fluida Vape dengan Geometri Smoke Line yang berbeda - Kooshartoyo, Meddy; Yohana, Eflita; Muchammad, Muchammad; Pane, Ivranza Zuhdi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
This research aims to analyze the flow visualization of the design of 2 types of smoke rake with vape fluid. The test model used was a three-dimensional NACA 4412 airfoil profile made from 10 mm thick flexyglass structural material, skin wrapped in epoxy resin with dimensions with chord length (C) = 151.52 mm, span width (S) = 300 mm, maximum thickness (t) = 19.18 mm made on a laboratory scale for wind tunnel testing purposes. Aerodynamic flow research was carried out at angles of attack (α) 5o, 100, 150 and 200 at wind speeds of 5 m/s, 10 m/s, and 15 m/s and 20 m/s. Several important parameters such as lift coefficient (CL), drag coefficient (CD), lift-drag ratio (L/D), in this study visually analyze the flow using the smoke method so that changes can be seen as the angle of attack (α) increases. The research results show that the drag coefficient (CD) and lift coefficient (CL) obtained using a numerical approach and testing in a wind tunnel from previous research data with this flow visualization research, changes in the angle of attack (α) have an effect on the leading edge area on the surface of the airfoil body, which in turn affects the overall aerodynamic characteristics. From the photo results, it can be seen that the difference in flow using the SR1 and SR2 smoke rake is greater.